Texas, its government and politics - Benton, Wilbourn E. (Prentice-Hall, 1966)
why is Texas like Texas and why do Texans act like Texans? answers to these questions are difficult because of the folk lore and myth that surrounds the state. In short, there is the mythical and actual state, as there is the professional and more nearly average Texas. also, there is a considerable difference between the theory and practice of Texas politics. However, in varying degrees, these considerations exist in other states. Be this as it may, answers to these questions are left for others to ponder. Rather than attempt such an ambitious inquiry, some of the trends and developments in Texas will be noted........